Characteristics of Carbon Nanospheres Prepared from Locally Deoiled Asphalt. (6th August 2013) - Ibrahim Mohammed, Mohammed; Ismaeel Ibrahim, Raheek; Mahmoud, Luma Hussein; Zablouk, Mumtaz Abdulahad; Manweel, Neeran; Mahmoud, Abeer
Abstract : Iraqi deoil asphalt as a source of carbon is used to prepare the carbon nanospheres (CNS) by chemical vapor deposition (CVD) method. Asphalt after further chemical treatment to remove aromatic oil and impurities was crushed, weighted and evaporated under inert atmosphere using argon. The vapor/argon mixture was allowed to pass through high temperature zone 900°C in quartz tube over CO/Al2 O3 catalyst material. The carbon precipitated from the decomposition of asphalt vapor was collected and identified using atomic force microscope (AFM), scanning electron microscope (SEM), X-ray diffractometer (XRD), BET surface area technique and atomic force microscope. A sphere shape of carbon (94%) with nanosize and diameter less than 100 nm with surface area of 360 m 2 /g has been obtained.